Design and Development of a Mobile Application for Marriage Counseling and Divorce Mediation at KUA Medan Tuntungan - Satria, Satria; Alda, Muhamad (Journal of Computer Networks, Architecture and High Performance Computing, 2024)
Marriage counseling is an effort that can be aimed at preparing prospective couples to establish a more serious relationship. Good communication involvement between the two prospective couples is one factor in building a solid foundation in marriage. Life after marriage has a big role and responsibility. Divorce can occur due to lack of readiness between the two prospective couples, so marriage counseling is very important so that prospective brides and grooms can prepare carefully for the relationship that will be carried out in the future. Therefore, this study builds a marriage counseling mobile application aimed at understanding the roles and responsibilities of marriage. This study itself uses a qualitative method by collecting, analyzing and reviewing valid data and information regarding marriage counseling for prospective couples. The waterfall method is used in this study as a system design where the waterfall is considered adaptable in the development of a marriage counseling mobile application accompanied by Unified Modeling Language (UML) modeling.